METHODOLOGICAL ASPECTS OF TEACHER TRAINING FOR THEATRICAL ACTIVITIES WITH PUPILS - Kazmirchuk, Natalia; Baranovska, Iryna; Mozgalova, Nataliia; Shcholokova, Olga; Podorozhnyi, Vadym (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The research was conducted as part of the project of Erasmus + (Module Jean Monnet) “EU experience of soft skills development of preschool and primary school age children by theatre activities in teacher training”.The purpose of the article is to find out the educational value of theatrical activities, to reveal the methodological aspects of preparing teachers for theatrical activities with pupils. The study used theoretical methods: analysis of psychological and pedagogical literature, synthesis, comparison, method of modeling and generalization of research results; diagnostic methods: interview, survey, observation, interview: methods of processing experimental data for quantitative and qualitative analysis of the results of diagnostic tests.The concept of “theatrical activity” is specified, the educational and developmental potential of theatrical activity is revealed, the technique of introduction of theatrical activity in practice of modern school is developed, methodical bases of preparation of teachers for theatrical activity with schoolchildren are opened.The results of empirical research have shown that most teachers do not use theatrical activities in their own pedagogical practice. Only certain elements are introduced in art and language lessons: staging of literary works or songs. We are convinced that theatrical activities are a powerful effective means of moral, aesthetic, promotes the development of social skills (soft skils), because it allows to involve students in various types of artistic creativity: literary, musical, visual, stage, choreographic. Through participation in theatrical performances, creative potential is revealed, high moral values are formed, sufficient communication skills are needed to model social behavior in the children's team, in the family and society as a whole. The study allowed to confirm the importance and practical feasibility of using theatrical activities as a means of education and development of youth